Hi!

# Mathematics - Algebra - Ask NCERT

Question-Mathematics - Algebra - Ask NCERT class 8 Algebraic Expressions and Identities with solution questions answer. All ncert questions Answers for class 8 subject Mathematics chapter Algebraic Expressions and Identities and topic Algebra

## If p = 2 - a, then prove that a3 + 6ap + p3 - 8 = 0

Asked on :18 November 2022:11:05:37 AM

## If p = 2 - a, then prove that a3 + 6ap + p3 - 8 = 0

-Added by Master Mind Mathematics » Algebra

Master Mind

Given: p = 2 - a

Putting the value of p into p(x)

P(x) = a3 + 6ap + p3 - 8 = 0

= a3 + 6a(2 - a) + (2 - a)3 - 8 = 0

=  a3 + 12a - 6a2 + 23 - 3x22xa + 3x2xa2 - a3 - 8 = 0

=  a3 + 12a - 6a2 + 8 - 12a + 6a2 - a3 - 8 = 0

= 0

Hence proved

-Answered by Master Mind On 18 November 2022:11:06:58 AM

## Solve the equation 6(7b - 4) = 60 for b.

Asked on :18 November 2022:11:06:33 AM

## Solve the equation 6(7b - 4) = 60 for b.

Given equation is 6(7b - 4) = 60  Step by Step explanation

7b - 4 = 606

7b - 4 = 10

7b = 10 + 4

7b = 14

b = 147 = 2 Answer

## On dividing Polynomials x3+2x2-5ax-7 and x3+ax2-12x+6 by (x+1) and (x-2) respectively gives remainder R1 and R2.  if 2R1+ R2 = 6 then find the value of a.

Asked on :18 November 2022:01:05:56 PM

## On dividing Polynomials x3+2x2-5ax-7 and x3+ax2-12x+6 by (x+1) and (x-2) respectively gives remainder R1 and R2.  if 2R1+ R2 = 6 then find the value of a.

-Added by Akki chauhan Mathematics » Algebra

Shalu Shukla -Answered by Shalu Shukla On 01 March 2019:03:47:38 PM

## Q1. Simplify;3a - 2b - ab - (a-b+ab)+ 3ab +b - a

Asked on :18 November 2022:01:06:07 PM

## Q1. Simplify;3a - 2b - ab - (a-b+ab)+ 3ab +b - a

-Added by Master Purushottam Mathematics » Algebra

Nishant Verma

3a-2b-ab-(a-b+ab)+3ab+b-a

3a-2b-ab-a+b-ab+3ab+b-a
take same terms like this
3a-a-a -2b+b+b -ab-ab+3ab
3a-a-a=a
-2b+b+b=0
-ab-ab+3ab= -2ab+3ab=ab
=a+0+ab
=a+ab
=a(1+b)

-Answered by Nishant Verma On 17 October 2019:02:39:08 PM

Master Purushottam

3a-2b-ab-(a-b+ab)+3ab+b-a

3a-2b-ab-a+b-ab+3ab+b-a
take same terms like this
3a-a-a -2b+b+b -ab-ab+3ab
3a-a-a=a
-2b+b+b=0
-ab-ab+3ab= -2ab+3ab=ab
=a+0+ab
=a+ab
=a(1+b)

-Answered by Master Purushottam On 22 August 2019:08:55:31 PM

Himanshi Verma

3a-2b-ab-(a-b+ab)+3ab+b-a

3a-2b-ab-a+b-ab+3ab+b-a
take same terms like this
3a-a-a -2b+b+b -ab-ab+3ab
3a-a-a=a
-2b+b+b=0
-ab-ab+3ab= -2ab+3ab=ab
=a+0+ab
=a+ab
=a(1+b)

-Answered by Himanshi Verma On 22 March 2019:05:17:37 PM

## Ask the Question that you Have?

#### Do you have a question to ask?

Mathematics - Algebra - Ask NCERT

You can see here all the solutions of this question by various user for NCERT Solutions. We hope this try will help you in your study and performance.

This Solution may be usefull for your practice and CBSE Exams or All label exams of secondory examination. These solutions or answers are user based solution which may be or not may be by expert but you have to use this at your own understanding of your syllabus.

## Search your Question Or Keywords

#### Do you have a question to ask?

You can ask your question or home work easily from ncert books any subject any chapter to go on Ask Question page.

User Earned Point: Select

## All Tags by Subjects:

Science (2380)
History (333)
Geography (311)
Economics (262)
Political Science (100)
Mathematics (410)
General Knowledge (5812)
Biology (94)
Physical Education (20)
Chemistry (118)
Civics (113)
Sociology (9)
Hindi (47)
English (371)
Physics (1435)
Other (98)
Accountancy (378)